Assessing Achievements and Planning for Progress: Report of the mid-term assessment meeting of AICCRA Gender and Social Inclusion - Huyer, Sophia; Gondwe, Therese (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
From November 28 – Decembr 2, AICCRA researchers met with the World Bank and the AICCRA independent Science Committee to assess mid-term progress. On December 2, 2022, researchers from the six country teams, regional programs and themes met to discuss progress, exchange experience and highlight issues for further exploration in gender and social inclusion.